Predictors of university students’ intention to participate voluntarily in an urban agriculture program - Tiraieyari, Neda; McLean, Gary N. (Common Ground Research Networks, 2017)
Urban agriculture has generated significant interest in developing countries to address concerns over food security. While attracting the participation of young people in agriculture has become a major challenge for many countries, few quantitative studies have been carried out on students’ participation in urban agriculture programs. Drawing on the theory of planned behavior, we surveyed 438 undergraduate students from a public university in Malaysia about their intention to join a new urban agriculture program. Hierarchical regression findings indicated that attitude, subjective norms, perceived barriers, and moral norms accounted for 39 percent of the variability in students’ intention to participate in the program beyond the contribution of, family involvement in agriculture, participation in on-campus activities, past volunteer experience, and gender. Attitude, subjective norms, and moral norms appear to be an important target to inspire students volunteering for the program.